Price and welfare theory - Hibdon, James E. (New York : McGraw-Hill, 1969)
The book is intended for undergraduate and first-year graduate students. Consistent with that purpose, it covers a somewhat greater range of topics than most texts, with sufficient rigor and clarity, we hope, to provide a sound introduction to them.
Includes bibliographical references and index.
rpm 02/11/2017
Loans
Keywords: Economics